Behavioural attitudes of three-wheeled taxi drivers towards mitigation of on-road air pollution in urban cities in Sri Lanka: a qualitative study from South Asia - Carukshi Arambepola; W D C Niroshini Adikaram (BMJ Publishing Group, 2024)
Objectives In recent years, urban areas across South Asia have experienced alarming levels of air pollution, primarily attributed to the rapid growth of motorised transportation. Three-wheeled taxis, commonly known as 'tuk-tuks', constitute a significant portion of the public transport system in Sri Lankan cities, making it crucial to understand the behavioural attitudes of their drivers in addressing on-road air pollution as they are key stakeholders in urban mobility and environmental sustainability. Therefore, this research aimed to contribute valuable insights into the behavioural attitudes of three-wheeled taxi drivers towards mitigation of on-road air pollution.Methods We recruited 67 three-wheeled taxi drivers to participate in semi-structured focus group interviews and in-depth interviews through purposive sampling. The sample size was determined on the basis of data saturation. We collected data from on-site note-taking, audio recording and transcribing the interviews, and subjected them to content thematic analysis manually.Result Behavioural attitudes for mitigation were mainly based on efforts to minimise on-road air pollution, perception of minimising on-road air pollution, knowledge, socio-demographic and legislative factors related to behaviour.Conclusion Behavioural attitudes on mitigation were multi-faceted. To minimise the hazards as well as mitigate air pollution, educating and supporting them financially and by inducing a behavioural change are recommended to safeguard their health.